Echocardiographic predictors of single versus dual MitraClip device implantation and long‐term reduction of mitral regurgitation after percutaneous repair. Issue 4 (14th March 2013) - Armstrong, Ehrin J.; Rogers, Jason H.; Swan, Christo H.; Upadhyaya, Deepa; Viloria, Esperanza; McCulloch, Charles; Slater, James; Qureshi, Mansoor; Williams, John; Whisenant, Brian; Feldman, Ted; Foster, Elyse
<x xml:space="preserve">Abstract</x> Objectives To describe predictors of the number of MitraClip devices implanted during percutaneous repair of mitral regurgitation (MR), and the long‐term reduction in MR. Background In the EVEREST trials, one or two MitraClip devices were implanted to reduce MR, as needed. Methods Preprocedural transthoracic echocardiograms (TTE) and transesophageal echocardiograms (TEE) of 233 subjects who received 1 or 2 MitraClip devices in the EVEREST II Randomized Trial and High‐Risk Study were analyzed. TEEs were reviewed for etiology of MR and pathoanatomic features of the valve, valve apparatus, and the regurgitant jet. Follow‐up MR was assessed by TTE postprocedure and at 12 months. Results Ninety‐seven subjects (42%) had two MitraClip devices implanted. Subjects with quantitatively more severe MR were more likely to receive two devices [mean regurgitant volume (RV) 45.9 ± 21.9 vs. 36.3 ± 18.5 mL, P <0.001]. On multivariate analysis, increased anterior leaflet thickness (OR 1.7 per mm, P = 0.007) and greater baseline RV (OR 1.21 per 10 mL, P = 0.01) were associated with increased odds of implanting two devices. The frequency of 2+ MR or less at discharge was similar regardless of the number of devices implanted. After propensity matching, patients had quantitatively similar MR at twelve‐month follow‐up, regardless of whether one or two MitraClip devices were implanted (P = 0.6). Conclusions Subjects with thicker anterior mitral leaflets and more severe MR were more likely to receive two MitraClip devices. Immediate and long‐term reduction in MR was similar regardless of the number of devices implanted at the time of the procedure. © 2012 Wiley Periodicals, Inc.